Potencial antagonista de rizobacterias pseudomonas spp nativas, frente a hongos patogénicos del cultivo de cacao (theobroma cacao l.). - Alarcón Montecé, Edwin Oswaldo (2016)
Phytophthora spp and black pod of Theobroma cacao L are caused by different fungi like; Moniliophthora roreri and Phytophthora spp, these are one of the major phytosanitary problems in areas where this area is cultivated. Considering the samples they were collected from two farms cocoa production more than 40 years of production, located in the Sectors; Quevedo and Buena Fe belonging to the province of Los Rios, bacterial isolates from cacao estate where bacteria containing characteristic fluorescence of the bacteria Pseudomonas spp in which were measured by criteria such as assessed and identified were performed; (Diameter, edge, etc.), physiological (is determined mediated temperature) in order to start the characterization of populations of the fungus in the country and have a bank of isolates for further research at different levels. Experiments were performed in the laboratory of biotechnology State Technical University of Quevedo. King B culture media and PDA was used (Papa takes agar) in liquid and solid state to assess growth and confrontations of bacteria and fungi. Bacteria were grown in culture media King b in liquid state for a period of 72 hours, and then be inoculated into boxes containing culture media PDA solid state in which fungi Moniliasis roreri and Phytophthora spp were sown, Some of the isolates tested showed antagonistic capacity characteristics of the bacteria Pseudomonas fluorescens, coincided with the bacteria that showed the greatest potential antagonistic to the fungus.